Elevated systemic levels of inflammatory cytokines in older women with persistent cervical human papillomavirus infection - Kemp, Troy J. (2010)
Background: Defects in lymphoproliferative responses to mitogens/antigens in women >45 years old with a persistent type-specific human papillomavirus (HPV) infection have been reported. Methods: To determine whether these defects were associated with altered cytokine profiles, plasma and peripheral blood mononuclear cell (PBMC) culture supernatants from 50 cases (oversampled for their reduced lymphoproliferative ability) and 50 uninfected controls (oversampled for their robust lymphoproliferative ability) were examined for 24 cytokines using multiplexed bead–based immunoassays and ELISA. Results: The following plasma cytokines were significantly increased in cases relative to controls (cases versus controls; median pg/mL): interleukin (IL)-6, 393.1 versus 14.5; IL-8, 1,128.5 versus 43.9; tumor necrosis factor-α (TNF-α), 164.1 versus 9.2; macrophage inflammatory protein-1α (MIP-1α), 1,368.9 versus 25.5; granulocyte macrophage colony-stimulating factor (GM-CSF), 13.8 versus 7.3; IL-1β, 8.3 versus 1.6 (all P < 0001);and IL-1α, 218.2 versus 169.5 (P = 0.02).We focused our analysis on the cytokines IL-6, IL-8, TNF-α, and MIP-1α due to their high fold change (>10) and highly statistically significant difference between cases and controls. Length of persistence or type of infection (high risk and low risk) did not affect these differences. IL-6, TNF-α,and MIP-1α levels were also increased in unstimulated PBMC culture supernatants from cases compared with controls (P < 0.05), however, the cytokine levels from phytohemagglutinin-stimulated PBMC culture supernatants were significantly lower in the cases (P < 0.0001). Conclusions: Persistent HPV infection in older women with evidence of immune deficit is associated with an increase in systemic inflammatory cytokines. Impact: Future studies are needed to determine whether the inflammatory profile is age dependent and to examine the role that inflammatory cytokines play in HPV-induced progression from infection to cervical cancer.